Evaluation of The Role of Internal Compliance Unit on The Effectiveness of Internal Control - Amy Sabrina Khairunnisa; Yan Rahadian (Riset Akuntansi dan Keuangan Indonesia, 2021)
This study aims to evaluate the second line roles in supporting the effectiveness of internal control based on its principles. In the Directorate General of Taxes (DGT), the Internal Compliance Unit serves as its second line of defense. The present study was conducted at the Internal Compliance Sub-directorate which is the Internal Compliance Unit Echelon I level at DGT. Descriptive qualitative research applying a deductive approach with a case study method was carried out to answer the research problems. The criteria used to evaluate the second line roles on the effectiveness of internal control refer to the publication of the Committee of Sponsoring Organization of Treadway Commission (COSO) in collaboration with the Institute of Internal Auditors (IIA) in July 2015 entitled “Leveraging COSO Across the Three Lines of Defense”. The results of the study shows that the operation of UKI in supporting the effectiveness of internal control is quite satisfactory. However, several principles have not been implemented optimally